Perceptions of drinking water access and quality in rural indigenous villages in Fiji. Issue 3 (2nd March 2022) - Nelson, Sarah; Thomas, Jacqueline; Jenkins, Aaron; Naivalu, Kelera; Naivalulevu, Timoci; Naivalulevu, Vilisi; Mailautoka, Kinikoto; Anthony, Shylett; Ravoka, Mereia; Jupiter, Stacy D.; Mangubhai, Sangeeta; Horwitz, Pierre; et al.
Abstract: Poor rural water quality is a health challenge in Fiji. A mixed-methods study in six iTaukei (Indigenous Fijian) villages was conducted to understand local perceptions of drinking water access and quality, how this changes drinking water source choices, and impacts of age and gender. Seventy-two household surveys, 30 key informant interviews (KIIs) and 12 focus group discussions (FGDs) were conducted. Household surveys revealed 41.7% of community members perceived their water as dirty and 76.4% perceived their water as clean. Two-thirds of households reported that they always or usually had enough water. FGDs and KIIs revealed water access and quality was influenced by population size, seasonality, and rainfall. Perceptions of water quality caused villages to shift to alternative water sources. Alignment of the qualitative and quantitative data identified four themes: sources and infrastructure, access, quality and contamination. There was mixed alignment of perceptions between access and quality between the household surveys, and KIIs and FGDs with partial agreement sources and infrastructure, and quality. Gender was found to influence perceptions of dirty water, contamination, and supply and demand. Perceptions of water quality and access shape decisions and choices for water sources and can be used to inform resilience and inclusive water strategies. HIGHLIGHTS: Seasonality impacts drinking water access and quality perceptions in Fijian villages. Limited drinking water supply and quality issues result in people needing to switch to alternative water sources. Grazing livestock and plantations near drinking water sources are perceived as sources of contamination. Perceptions of water quality highlight the importance of a participatory approach to the development of water safety plans. Graphical Abstract